Theory Research on Visual Communication Design of Urban Public Space under the Concept of Social Design - Wang, Chun (International Journal of Social Sciences and Public Administration, 2024)
Through observation and analysis of modern urban public spaces, we can find that design is not only a combination of appearance and functionality, but also a profound understanding and response to society, culture, and the environment. The social design concept emphasizes the principle of people-oriented design, pursuing the inclusiveness, interactivity, and sustainability of public spaces, and shaping the identity and shared experience of urban spaces through visual language and symbol systems. This article will explore how to implement the concept of social design in visual communication design, and explore its impact on the quality of life, social cohesion, and urban image of urban residents. The ultimate goal is to provide practical guidance and inspiration for urban planners, designers, and decision-makers, promoting sustainable development of public spaces and social harmony.